Caracterización palinológica y viabilidad polínica de Physalis peruviana L. y Physalis philadelphica L. - Lagos Burbano, TC; Caetano, C.M.; Vallejo Cabrera, Franco Alirio; Muñoz, J.E.; Criollo Escobar, H; Olaya, Cristian A. (2005)
Physalis peruviana L. and P. philadelphica Lam. represent two Solanaceae species which are economically important for Colombia and Mexico, respectively. Little is currently known regarding P. peruviana and P. philadelphica palynology and pollen viability. This work was thus aimed at characterising these two species pollen grains and determining pollen viability in contrasting cold and warm climate conditions. Acetolysis (light microscopy) and scanning electron microscopy were employed for pollen characterisation. The following traits were determined: polar axis, equatorial diameter, aperture number, position and character (NPC), apocolpus/apoporus side, pollen morphology, axis and equatorial contour, polar area and aperture and pollen types. This led to describing and characterising the pollen grains of the genotypes being studied. Flower fixation during anthesis, followed by acetocarmin staining, was used for establishing pollen viability; observations were made by light microscope. The two species displayed a medium-sized pollen grain zono-tricolporate in P. peruviana and a small-sized one in P. philadelphica. Marginal environments reduced pollen viability but did not affect fertility.